2002
DOI: 10.1002/jcb.10221
|View full text |Cite
|
Sign up to set email alerts
|

Specific induction of heat shock protein 27 by glucocorticoid in osteoblasts

Abstract: It is generally recognized that osteoporosis is a common complication of patients with glucocorticoid excess and that glucocorticoid receptor is associated with heat shock protein (HSP) 70 and HSP90 in a heterocomplex. In the present study, we investigated whether glucocorticoid induces HSP27, HSP70, and HSP90 in osteoblast-like MC3T3-E1 cells. Dexamethasone time-dependently increased the levels of HSP27, while having no effect on the levels of HSP70 or HSP90. The effect of dexamethasone was dose-dependent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
4
14
1
1
Order By: Relevance
“…4). Other studies have demonstrated that p38 MAP-kinase-dependent osteoblast differentiation is important, 46,51,52 even though OSX mRNA expression was only suppressed by LIPUS stimulation at 24 h in our study. However, the strongest mineral accumulation was apparent in LIPUS-treated osteoblasts.…”
Section: Fig 5 Western Blot Analysiscontrasting
confidence: 60%
“…4). Other studies have demonstrated that p38 MAP-kinase-dependent osteoblast differentiation is important, 46,51,52 even though OSX mRNA expression was only suppressed by LIPUS stimulation at 24 h in our study. However, the strongest mineral accumulation was apparent in LIPUS-treated osteoblasts.…”
Section: Fig 5 Western Blot Analysiscontrasting
confidence: 60%
“…Previous findings have shown that stimuli-induced activation, not basal repression͞inhibition, of the MEK pathways can repress GR (45)(46)(47)(48)(49)(50)(51)(52). However, one study has shown that SB203580 prevents Dex-induced Hsp27 production in osteoclasts (53), suggesting that the relationship between LeTx repression of GR and p38 requires further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports showed that p38-MAPK is involved in apoptosis [14,23] and activated during the GC-induced apoptosis [15,19]. Recent studies demonstrated that p38-MAPK plays many critical roles in apoptosis and survival in osteoblasts [16,17].…”
Section: Discussionmentioning
confidence: 98%
“…The p38-MAPK activation is essential for differentiation of osteoblasts [13]. However, p38-MAPK phosphorylation in osteosarcoma and osteoblasts cells is related to apoptosis through the subsequent activation of caspase-3 [14,15]. The p38-MAPK has been shown to play many important roles in apoptosis and survival in osteoblasts [16,17].…”
Section: Introductionmentioning
confidence: 99%